2007
DOI: 10.1080/17482960701223113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of motor fatigue: Normative values and comparison with prior‐polio patients

Abstract: Motor fatigue is a common complaint of polio survivors and has a negative impact on activities of daily living. The aim of this study was to establish a normative database for hand grip strength and fatigue and to investigate differences between prior-polio subjects and normal controls. Static and dynamic hand grip fatigue and maximum voluntary isometric contraction (MVIC) of hand grip were measured in subjects with a prior history of polio (n = 44) and healthy controls (n = 494). A normative database of fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Each test was completed if the participant had adequate power to generate a resistance against the load cell or dynamometer; otherwise, a score of zero was given. Hand grip static fatigue, of the dominant hand, was measured by maintaining maximal hand grip for 30 s and percentage fatigue was calculated using fatigue index 3 (Figure 1), described in detail previously (Meldrum et al, 2007b;Schwid et al, 1999). The same method was applied to the dominant side lower limb movements, which were strong enough to generate a resistance against the load cell, providing static fatigue measurements over 30 s for hip flexion, knee flexion and extension and ankle dorsiflexion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each test was completed if the participant had adequate power to generate a resistance against the load cell or dynamometer; otherwise, a score of zero was given. Hand grip static fatigue, of the dominant hand, was measured by maintaining maximal hand grip for 30 s and percentage fatigue was calculated using fatigue index 3 (Figure 1), described in detail previously (Meldrum et al, 2007b;Schwid et al, 1999). The same method was applied to the dominant side lower limb movements, which were strong enough to generate a resistance against the load cell, providing static fatigue measurements over 30 s for hip flexion, knee flexion and extension and ankle dorsiflexion.…”
Section: Methodsmentioning
confidence: 99%
“…The power calculation was based on published scores of mean hand grip static fatigue of 29.9% in Polio survivors and 23.7% in controls from 45 to 70 years, with a SD of 5.9% (Meldrum et al, 2007b). This calculation indicated that 26 participants in each group would be required to achieve a power of 0.95 and Type I error of 0.05.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The muscle weakness often affects the lower limbs, but in approximately 60% of persons with late effects of polio, muscle weakness also occurs in the upper limbs [4]. Studies have shown that persons who had polio in the past have significantly reduced grip strength [4,5] and isometric elbow muscle strength [6,7] compared with healthy persons, which has an impact on their ability to perform daily activities with their hands [4].…”
Section: Introductionmentioning
confidence: 99%